Molecular-based laboratory testing confer accuracy over microscopical testing for tick identification - Isaac Singh; Min-Kuang Lee; Emily Kon; Navdeep Chahil; Martin Cheung; Catherine Hogan; Muhammad Morshed (International Journal for Parasitology: Parasites and Wildlife)
As per published literature, the Ixodes pacificus tick is the primary Lyme disease vector in British Columbia (BC), while the Ixodes scapularis tick species is the dominant vector on the East Coast of Canada, with no I. scapularis presence seen in BC. However, a recent publication reported presence of I. scapularis in BC which initiated this study to determine the accuracy of the microscopic identification of ticks received in the BC Centre for Disease Control (BCCDC) Public Health Laboratory and compare morphologic methods to molecular methods. Molecular testing uses a real-time PCR assay to amplify the internal transcribed spacer 2 region as a screening method for I. scapularis; while Sanger sequencing tests the cytochrome c oxidase subunit 1 gene for species confirmation. Of the 209 ticks tested, 74% were I. pacificus, 3.8% were I. scapularis, and 22% were other genus including Amblyomma. Phylogenetic analysis was achieved through Sanger sequencing, confirming the accuracy of the real-time PCR assay. Notably, 6 of 8 I. scapularis tick’s hosts had clear travel history outside BC, while the 2 remaining have no confirmed travel. Both the microscopic and molecular identification methods suggest that I. pacificus ticks are dominant in BC and ticks identified as I. scapularis have host travel history outside of BC. This study further underscores the importance of tick surveillance as global human travel and sometimes along with their pets facilitate tick migration.